Educadores para além do urbano: condições de trabalho docente na educação básica rural de Mazagão-AP - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2026)
This research analyzes the working conditions of teachers in rural schools in the municipality of Mazagão, in the state of Amapá, considering the structural determinations of neoliberalism and its impacts on public education. It starts from the understanding that rural education, historically marked by precariousness and subordination to the demands of capital, is still far from the paradigm of Rural Education as a counter-hegemonic political-pedagogical project linked to the struggles of peasant peoples. The general objective is to understand how the material, institutional, and pedagogical conditions of teaching work are configured in the schools investigated, problematizing the contradictions between the legal framework that ensures the right to rural education and the concrete reality experienced by teachers. The research adopts a qualitative approach, based on historical-dialectical materialism, articulating document analysis, observation of school units, and semi-structured interviews with teachers from the municipal network. The theoretical framework engages with authors critical of education, labor, and the State, such as Karl Marx, Saviani, Arroyo, Caldart, Frigotto, Antunes, Harvey, and Laval, seeking to understand the phenomenon in its historical and social totality. The results highlight structural precariousness, fragile employment ties, insufficient specific training policies, and the incidence of managerial models that disregard territorial particularities. It is concluded that teaching work constitutes a space of intense contradictions, marked simultaneously by precariousness and resistance, requiring structuring public policies that guarantee professional valorization, territorial justice, and the consolidation of an emancipatory project for Rural Education.
Keywords: Políticas Educacionais; Trabalho Docente; Educação do Campo; Educação rural; CNPQ::CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO; ODS 4 – Educação de qualidade; ODS 8 – Trabalho decente e crescimento econômico; ODS 10 – Redução das desigualdades; ODS 16 – Paz, justiça e instituições eficazes